The Effect Of Service Quality, Brand Image, Customer Satisfaction On Customer Loyalty At Indomaret Minimarket - Rizki Maulana; Asma’I Ishak (International Journal of Economics, Business and Innovation Research, 2025)
This research aims to examine the influence between service quality, brand image, customer satisfaction and customer loyalty at Indomaret. In this research, the target is Indonesian citizens who have or have not purchased at the Indomaret Minimarket. There were 200 respondents with the criteria of women and men aged 16 to over 40 years who had or had not shopped at the Indomaret Minimarket. Survey data was obtained using an online questionnaire via Google Form. The data analysis method used for this research is Structural Equation Modeling (SEM) in the AMOS 29 program. The research results prove that service quality has an effect on brand image and service quality has an effect on customer satisfaction.